2022
DOI: 10.33724/zm.1029470
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Changes of Organic Crops Production in Turkey

Abstract: Agricultural production is a vital need in terms of ensuring the continuity of the human population and meeting their requirements. Yet, the applications during agricultural production have a determining role on the quality of the final product. In addition to the amount of agricultural production and its economic value, the quality of the obtained product is very important. In this sense, it is known that the products produced with the organic agricultural practices are more nutritious, high quality, they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The cultivation of agricultural practices can affect the phytochemical content, structure, taste, aroma, color and thus drying properties of the products (Asami et al, 2003;Keskin et al, 2021a;Arslan, 2022). Bickel and Rossier (2015) reported that organic products are more nutritious than conventional varieties.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of agricultural practices can affect the phytochemical content, structure, taste, aroma, color and thus drying properties of the products (Asami et al, 2003;Keskin et al, 2021a;Arslan, 2022). Bickel and Rossier (2015) reported that organic products are more nutritious than conventional varieties.…”
Section: Introductionmentioning
confidence: 99%